2020
DOI: 10.1097/j.pain.0000000000002121
|View full text |Cite
|
Sign up to set email alerts
|

Are you in pain if you say you are not? Accounts of pain in Somali–Canadian women with female genital cutting

Abstract: As a rite of passage to womanhood, 2 million girls undergo female genital circumcision (FGC)—the tradition of cutting, and often removing parts of the vulva—every year. The current study is the first to focus on the connection between peripheral nerve damage and chronic neuropathic pain in women with FGC. We used mixed methods—quantitative, qualitative, and physiological—to study chronic pain in Somali–Canadian women (N = 14). These women have the most extensive form of FGC, which includes removal of the glans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
0
12
1
Order By: Relevance
“… 35 A recent study showed that a small sample of Somali-Canadian infibulated women reported low pain levels on validated pain questionnaires and reported good general health while having pain thresholds as low as other women with chronic vulvar pain during quantitative sensory pain testing in the vulvar area. 25 Only when the participants were handed open-ended questionnaires, leaving space for self-expression of pain, did they report chronic disabling daily pain. 25 In our pouplation, vulvar pain was linked to infibulation and vulvar scar complications, such as cysts, neuromas, scar tissue and bridles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 35 A recent study showed that a small sample of Somali-Canadian infibulated women reported low pain levels on validated pain questionnaires and reported good general health while having pain thresholds as low as other women with chronic vulvar pain during quantitative sensory pain testing in the vulvar area. 25 Only when the participants were handed open-ended questionnaires, leaving space for self-expression of pain, did they report chronic disabling daily pain. 25 In our pouplation, vulvar pain was linked to infibulation and vulvar scar complications, such as cysts, neuromas, scar tissue and bridles.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Only when the participants were handed open-ended questionnaires, leaving space for self-expression of pain, did they report chronic disabling daily pain. 25 In our pouplation, vulvar pain was linked to infibulation and vulvar scar complications, such as cysts, neuromas, scar tissue and bridles. As we present in another manuscript currently under review, surgical excision of such complications can reduce and treat such pain symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have stated that patients may feel pain despite local anesthetic interventions. During the preparation of this publication, there were 9 studies on circumcision in Pubmed in 2021, 5 of which focused on pain (6)(7)(8)(9)(10)(11)(12) .…”
Section: Discussionmentioning
confidence: 99%
“…In their critical analysis of neuroscience, neurofeminists have emphasized that critical race analysis must be considered in any investigation aiming to understand and ultimately dismantle inequitable sexed/gendered conditions ( Roy, 2012 ; Kuria, 2014 ; Rippon et al, 2014 ), and as our discussion highlights, research in neuroscience that is informed by intersectionality must expand its focus beyond sex/gender and race to include a wider spectrum of intersecting and marginalized identities. With the exception of a recent pain study conducted with Somali-Canadian women with female genital cutting (further detailed below, Perovic et al, 2021 ), to date, there are no neurofeminist parallels to this type of research ( Fitsch et al, 2020 ).…”
Section: Research Theme #1: How Social Structures Create Health Inequality In Individuals With Intersecting Social Identitiesmentioning
confidence: 99%